PENINGKATAN HASIL AKREDITASI PRODI PENDIDIKAN BAHASA ARAB STAI NURUL IMAN BOGOR MELALUI PENDAMPINGAN TELAAH KURIKULUM - Zuriyati; Endry Boeriswati; Zainal Rafli; Nuruddin; Yumna Rasyid; Muhammad Kamal; Ahmad Rizki Nugrahawan; Ahmad Zaki Munibi; Haris Hamdani; Mariani (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Negeri Jakarta, 2024)
Abstract This community service activity aims to improve the accreditation results of the Arabic Language Education study program at STAI Nurul Iman Bogor through curriculum review assistance. Through a participatory approach, the service team works with managers and teaching staff to identify the strengths and weaknesses of the existing curriculum, and design curriculum updates that are in accordance with the needs and latest developments in Arabic language education. The process of improving accreditation results through mentoring is carried out in the form of interactive counseling with material on improving the quality of study programs towards excellence, Arabic curriculum development, Arabic language learning methodology, and Arabic literature learning methodology. The results obtained from this activity include the participants having additional knowledge related to the preparation of study program accreditation towards excellence by practicing filling out accreditation forms. The participants also have references in implementing the methodology of learning Arabic language and literature through a practice so that they are ready to improve their teaching creatively. The experience and results of this activity can also be used as a reference for similar study programs in various other educational institutions. Keywords: curriculum review; quality improvement; Arabic language learning; learning Arabic literature Abstrak Kegiatan pengabdian kepada masyarakat ini bertujuan untuk meningkatkan hasil akreditasi prodi Pendidikan Bahasa Arab STAI Nurul Iman Bogor melalui pendampingan telaah kurikulum. Melalui pendekatan partisipatif, tim pengabdi bekerjasama dengan para pengelola dan tenaga pengajar untuk mengidentifikasi kekuatan dan kelemahan kurikulum yang ada, serta merancang pembaruan kurikulum yang sesuai dengan kebutuhan dan perkembangan terkini dalam pendidikan bahasa Arab. Proses peningkatan hasil akreditasi melalui pendampingan dilakukan dalam bentuk penyuluhan yang interaktif dengan materi peningkatan kualitas prodi menuju unggul, pengembangan kurikulum bahasa Arab, metodologi pembelajaran bahasa Arab, dan metodologi pembelajaran sastra Arab. Hasil yang diperoleh dari kegiatan ini antara lain para peserta telah memiliki pengetahuan tambahan terkait penyiapan akreditasi prodi menuju unggul dengan mempraktikkan pengisian borang akreditasi. Para peserta juga telah memiliki referensi dalam mengimplementasikan metodologi pembelajaran bahasa dan sastra Arab melalui sebuah praktik sehingga mereka siap meningkatkan pengajarannya secara kreatif. Pengalaman dan hasil dari kegiatan ini juga dapat dijadikan sebagai referensi bagi program studi sejenis di berbagai institusi pendidikan lainnya. Kata Kunci: telaah kurikulum; peningkatan mutu; pembelajaran bahasa Arab; pembelajaran sastra Arab